(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the theoretical aspects of teaching methods, in particular, the communicative orientation in teaching a foreign language. The methodological principles of communicative methodology are mentioned: interrelated aspects of the study of foreign language culture, including the complex nature of foreign language culture in the manifestation of unity and interrelation of its educational, cognitive, educational and developmental aspects.